Synthesis of Silver-Doped Titanium TiO2 Powder-Coated Surfaces and Its Ability to Inactivate Pseudomonas aeruginosa and Bacillus subtilis. (28th February 2013) - Khan, Saman; Qazi, Ishtiaq A.; Hashmi, Imran; Awan, M. Ali; Zaidi, Najum-us-Sehar Sadaf
Abstract : Hard, nonporous environmental surfaces in daily life are now receiving due recognition for their role in reducing the spread of several nosocomial infections. In this work, we established the photokilling effects of 1% silver-doped titanium dioxide TiO2 . The nanoparticles synthesized by liquid impregnation method were characterized using X-ray diffraction (XRD), energy dispersive spectroscopy (EDS), and scanning electron microscopy (SEM). The Ag-TiO2 nanoparticle coatings that have been applied on glass and venetian blind surfaces were effective in generating a loss of viability of two bacteria ( Pseudomonas aeruginosa and Bacillus subtilis ) after two hours of illumination under normal light in the visible spectrum. Such surfaces can be applicable to medical and other facilities where the potential for infection should be controlled.